Clinical Practice Guidelines for Cardiopulmonary and Cerebral Resuscitation. - Victor Rene Navarro Machado; Omar Bárbaro Rojas Santana; Alba Enseñat Álvarez; Arelys Falcón Hernandez (Medisur)
Clinical Practice Guidelines for Cardiopulmonary and Cerebral Resuscitation. It is the group of procedures that should be accomplished to restore circulation and ventilation in a patient with cardiac arrest, including actions to reintegrate upper neurological functions after restoring cardiac function. This document includes a review of concepts, aetiology and updates the main clinical aspects related with diagnosis and treatment aimed at the post-resuscitation syndrome. It includes assessment guidelines focused on the most important aspects to be accomplished.